Adaptation of Local Cultural Elements in Arabic Language Teaching Materials for Higher Education - Muhammad Naufal Ihsan; Dendodi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The availability of contextual textbooks in the form of local culture is very important, especially in learning Arabic, so that they are easy to understand because they are relevant to the environment. This research is focused on uncovering local cultural element material in the Ta'bir book from Silsilah Ta'lim Al-Lughah Al -' Arabiyah level 1 and describing the steps for adapting local cultural element content into Arabic language teaching material at Ma'a higher education institutions. had Imam Nawawi Al-'Aly Kubu Raya. This research is based on local cultural content which is adapted based on the two Arabic language learning theories in textbooks. The type of research used is descriptive qualitative with literature review data collection techniques. The findings of this research show that the text data on local cultural discourse in the book is 0% of external and internal cultural types, therefore the researcher describes 4 steps in adapting local cultural elements in Arabic language learning teaching materials in higher education.